Europeanisation of the contemporary far right : generation identity and fortress Europe - Nissen, Anita (Routledge studies in extremism and democracy, 2022)
Introduction: Europeanisation, the Far Right, and the 'Refugee Crisis' -- Social Movement Europeanisation and Far-Right Collective Action, Coalition-Building, and Frames -- Introducing Generation Identity: Origins, Resources, Opportunities, and Protest Actions -- Introducing Fortress Europe: Origins, Resources, Opportunities, and Protest Actions -- Framing Generation Identity: Shared Threat Perceptions and Visions of a European 'Us' of Ethnically Homogeneous Peoples -- Framing Fortress Europe: A 'Resistance' Movement against Islam and the Political Mainstream -- Europeanisation of Generation Identity's Collective Action: Jointly Mobilising in the Defence of Europe -- Europeanisation of Fortress Europe's Collective Action: Domestic Protests against the 'Islamisation' of Europe -- The Trans-European Generation Identity Coalition: Sustained by a Strong Leadership -- The Fortress Europe Network: Event-Specific and Lacking Professional Leadership -- Conclusion: Far-Right Europeanisation?